Tongue prosthesis after total glossectomy: a case report - Nascimento, Victor Alves [UNESP]; Oliveira, Jovânia Alves; Oliveira, Amanda Rosa de; Munhoz, Maira Foresti Vieira; Haddad, Marcela Filié (My University, 2024)
Squamous cell carcinoma (SCC) is the type of cancer that most frequently affects the oral cavity, mainly in men older than 50 years of age. Treatment for oral SCC often involves surgical excision of the affected margins, resulting in mutilation that affects the patient’s quality of life. The objective of this case report is to describe the prosthetic treatment of a 56-year-old man who underwent total glossectomy, resulting in speech and swallowing difficulties. The proposed treatment was a tongue prosthesis retained by orthodontic clasps on the mandibular first molars. After maxillary and mandibular complete-arch impressions were performed and casts were prepared for prosthetic planning, an acrylic resin plate and 3 tongue prototypes were fabricated. Esthetic and functional tests were carried out, and 2 tongue models (1 for speech and 1 for eating) were selected for acrylization, finishing, and polishing. After placement of the prostheses, the patient was referred for followup with a speech therapist to improve his adaptation with the prostheses. The patient was satisfied with the prostheses and able to perform the functions of chewing, swallowing, and speech production, which helped in his social reintegration and improved his quality of life.
Keywords: glossectomy; maxillofacial prosthesis; rehabilitation; tongue